2021
DOI: 10.1371/journal.pone.0257473
|View full text |Cite
|
Sign up to set email alerts
|

Mild phenotype of knockouts of the major apurinic/apyrimidinic endonuclease APEX1 in a non-cancer human cell line

Abstract: The major human apurinic/apyrimidinic (AP) site endonuclease, APEX1, is a central player in the base excision DNA repair (BER) pathway and has a role in the regulation of DNA binding by transcription factors. In vertebrates, APEX1 knockouts are embryonic lethal, and only a handful of knockout cell lines are known. To facilitate studies of multiple functions of this protein in human cells, we have used the CRISPR/Cas9 system to knock out the APEX1 gene in a widely used non-cancer hypotriploid HEK 293FT cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…Interestingly, emerging studies reported that partial Ape1 deficiency did not detectably affect the replication of HeLa cells, CH12F3 cells, HEK293 FT cells, HCT116 cells, and HCC1937 cells [ 57 , 58 , 59 , 60 ]. The first report of a viable APEX1 -KO was in a study addressing the role of Ape1 in AID-mediated class switch recombination in Ig genes [ 61 ], in which a rescue vector expressing Ape1 was maintained while all 3 APEX1 copies in the hypotriploid mouse line CH12F3 were deleted.…”
Section: Ape1 Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, emerging studies reported that partial Ape1 deficiency did not detectably affect the replication of HeLa cells, CH12F3 cells, HEK293 FT cells, HCT116 cells, and HCC1937 cells [ 57 , 58 , 59 , 60 ]. The first report of a viable APEX1 -KO was in a study addressing the role of Ape1 in AID-mediated class switch recombination in Ig genes [ 61 ], in which a rescue vector expressing Ape1 was maintained while all 3 APEX1 copies in the hypotriploid mouse line CH12F3 were deleted.…”
Section: Ape1 Overviewmentioning
confidence: 99%
“…Surprisingly, removal of the rescue plasmid did not affect cell proliferation, although the complete APEX1 -KO did sensitize cells to the simple alkylating agent methylmethane sulfonate (MMS) [ 61 ]. Recently, a total knockout of APEX1 in (human) HEK293 FT cells (which also have three copies of the gene) gave a very similar result to that of CH12F3 cells; there was no impact on cell proliferation and only a modest increase in MMS sensitivity [ 59 ]. A severe Ape1 knockdown leads to more unrepaired AP sites in genomic DNA [ 56 ], but the mRNA levels of both monofunctional DNA glycosylases (e.g., MutyH, Ung) and multifunctional DNA glycosylases (e.g., Ogg1 and Neil2) were not significantly changed [ 54 , 59 , 62 ].…”
Section: Ape1 Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain-specific knockout mice develop normally in utero but die soon after birth from massive oxidative brain damage [ 34 ]. Several knockout cell lines of human and mouse origin have been reported, their phenotypes ranging from rather mild sensitivity to genotoxic agents to quick, spontaneous apoptosis [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%